2017
DOI: 10.1109/tac.2016.2599434
|View full text |Cite
|
Sign up to set email alerts
|

Contact-Force Control of a Flexible Timoshenko Arm in Rigid/Soft Environment

Abstract: This paper discusses a contact-force control problem of a one-link flexible arm. This flexible arm includes a Timoshenko beam, and thus we call it the flexible Timoshenko arm. The primary aim is to control the contact force at the contact point. To do so, we first apply our previously proposed force controller, which exponentially stabilizes the closed-loop system of a flexible Euler-Bernoulli arm, to the force-control problem of the flexible Timoshenko arm. We then show that our previously proposed force cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…Theorem 1: For the OTEC system (9)- (12), with the bounded initial conditions and boundary controls (13)- (19), the following conclusions can be obtained:…”
Section: Construct the Lyapunov Candidate Function Asmentioning
confidence: 92%
See 1 more Smart Citation
“…Theorem 1: For the OTEC system (9)- (12), with the bounded initial conditions and boundary controls (13)- (19), the following conclusions can be obtained:…”
Section: Construct the Lyapunov Candidate Function Asmentioning
confidence: 92%
“…It will weaken the performance of the OTEC system, even destroy this flexible structure. Recent researches about the flexible structures have been developed [17], [18], [19], [20], [21]. In [22], the authors studied the vibration problem and the stochastic disturbances for a flexible marine riser system.…”
Section: Introductionmentioning
confidence: 99%
“…Endo et al [10]- [12] used a simple boundary feedback controller consisting of a bending moment at the base of a flexible arm, and its time derivative, and implemented an analytical model for the force control problem for a constrained flexible arm. The exponential stability of the closed-loop system using this simple feedback control was analytically demonstrated therein.…”
Section: Introductionmentioning
confidence: 99%
“…Endo et al. dedicated to research on the contact‐force control for Timoshenko beam and showed us several difference controllers .…”
Section: Introductionmentioning
confidence: 99%
“…He et al discussed the design of boundary controller for Timoshenko beam and some flexible beams under input and output constraints [22][23][24][25][26]. Endo et al dedicated to research on the contact-force control for Timoshenko beam and showed us several difference controllers [27,28].…”
Section: Introductionmentioning
confidence: 99%